Single-Dose Messenger RNA Vaccine Effectiveness Against Severe Acute Respiratory Syndrome Coronavirus 2 in Healthcare Workers Extending 16 Weeks Postvaccination: A Test-Negative Design From Québec, Canada. (30th August 2021) - Carazo, Sara; Talbot, Denis; Boulianne, Nicole; Brisson, Marc; Gilca, Rodica; Deceuninck, Geneviève; Brousseau, Nicholas; Drolet, Mélanie; Ouakki, Manale; Sauvageau, Chantal; Barkati, Sapha; Fortin, Élise; et al.
Abstract: Background: In Canada, first and second doses of messenger RNA (mRNA) vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were uniquely spaced 16 weeks apart. We estimated 1- and 2-dose mRNA vaccine effectiveness (VE) among healthcare workers (HCWs) in Québec, Canada, including protection against varying outcome severity, variants of concern (VOCs), and the stability of single-dose protection up to 16 weeks postvaccination. Methods: A test-negative design compared vaccination among SARS-CoV-2 test–positive and weekly matched (10:1), randomly sampled, test-negative HCWs using linked surveillance and immunization databases. Vaccine status was defined by 1 dose ≥14 days or 2 doses ≥7 days before illness onset or specimen collection. Adjusted VE was estimated by conditional logistic regression. Results: Primary analysis included 5316 cases and 53 160 controls. Single-dose VE was 70% (95% confidence interval [CI], 68%–73%) against SARS-CoV-2 infection; 73% (95% CI, 71%–75%) against illness; and 97% (95% CI, 92%–99%) against hospitalization. Two-dose VE was 86% (95% CI, 81%–90%) and 93% (95% CI, 89%–95%), respectively, with no hospitalizations. VE was higher for non-VOCs than VOCs (73% Alpha) among single-dose recipients but not 2-dose recipients. Across 16 weeks, no decline in single-dose VE was observed, with appropriate stratification based upon prioritized vaccination determined by higher vs lower likelihood of direct patient contact. Conclusions: One mRNA vaccine dose provided substantial and sustained protection to HCWs extending at least 4 months postvaccination. In circumstances of vaccine shortage, delaying the second dose may be a pertinent public health strategy. Abstract : In a test-negative design among healthcare workers in Quebec, Canada, 1 mRNA vaccine dose reduced the risk of severe acute respiratory syndrome coronavirus 2 illness by about three-quarters and associated hospitalization by >95%, with substantial single-dose protection persisting at least 4 months postvaccination.